2009
DOI: 10.1063/1.3171933
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on thermoelectric properties of graphene nanoribbons

Abstract: We investigate the thermoelectric properties of graphene nanoribbons (GNRs) by solving atomistic electron and phonon transport equations in the nonequilibrium Green’s function formalism. The dependence of thermopower on temperature and chemical potential is compared to that of graphene, which shows the important role of quasi-one-dimensional geometry in determining the thermoelectric properties of a GNR. The edge roughness and lattice vacancy are found to increase the thermopower but decrease the thermoelectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
168
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(190 citation statements)
references
References 13 publications
16
168
3
3
Order By: Relevance
“…It is shown that the maximum of ZT values occurs at the bottom or top of energy band, which is due to the higher Seebeck coefficient and less electronic thermal conductance. This is different from the previous work 11 in which the maximum of ZT values appears only at the bottom of bands. These results indicate that the higher ZT value can be obtained by controlling the electronic behavior in the edges of energy bands.…”
Section: Copyright 2011 Author(s) This Article Is Distributed Under contrasting
confidence: 54%
See 1 more Smart Citation
“…It is shown that the maximum of ZT values occurs at the bottom or top of energy band, which is due to the higher Seebeck coefficient and less electronic thermal conductance. This is different from the previous work 11 in which the maximum of ZT values appears only at the bottom of bands. These results indicate that the higher ZT value can be obtained by controlling the electronic behavior in the edges of energy bands.…”
Section: Copyright 2011 Author(s) This Article Is Distributed Under contrasting
confidence: 54%
“…However, due to the high thermal conductivity, perfect GNRs usually have a very small ZT value. 5 For actual applications, some efforts have been done to enhance the ZT value through artificial manipulation such as introducing disorder 11,12 and nanojuctions. 13 However, since the electronic conductance can also be destroyed by these treatments, very little progress was obtained.…”
Section: Copyright 2011 Author(s) This Article Is Distributed Under mentioning
confidence: 99%
“…The Seebeck coefficient displays peak values 75 of the order of 0.1 − 1.5 mV/K, which is similar to what has been obtained for other carbon-based nanosystems and molecular contacts. 8,34,76 For bulk materials the thermoelectric figure of merit is defined in terms of the electrical and thermal conductivities, σ e ,σ t , as ZT = T σ e S 2 /σ t . For the ballistic graphene systems we can write it in terms of their respective conductances by introducing a width, effective length, and thickness, ZT = T G e S 2 /(κ e + κ ph ).…”
Section: Thermoelectric Figure Of Meritmentioning
confidence: 99%
“…24 Several ways to reduce the thermal conductivity have already been examined, such as interface mismatching between graphene and nanoribbons, 25,26 the presence of isotopes, [27][28][29][30] cross-plane phonon coupling in a few layers of graphene, 31 strain, 32 random hydrogen vacancies in graphene, 33 and point defects. [34][35][36] Edge disorder has been predicted theoretically to suppress heat conductance of graphene nanoribbons, [37][38][39] and ZT exceeding 3 has been theoretically predicted for such systems in the diffusive limit. 40 GALs have been proposed as a flexible platform for creating a semiconducting material with a band gap which can be tuned by varying the antidot size, shape, or lattice symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, thermoelectric phenomena in graphene nanoribbons have been widely studied [22][23][24][25][26]. In this context, Mazzamuto et al have analyzed thermal and electrical properties of perfect graphene nanoribbons as a function of their width and edge orientation [26].…”
Section: Introductionmentioning
confidence: 99%